Influence of vagus nerve traction on perinatal cervix maturity and on the occurrence of spontaneous labor in female primiparous in physiological pregnancy - Anna Sass; Martyna Mączka; Michał Matuszak (Kazimierz Wielki University, 2018)
Objective: Operational aim: To assess the impact of vagal nerve traction on perinatal maturity of the cervix, among female primiparous in physiological pregnancy. Cognitive aim: Evaluation of the influence of vagus nerve traction on the occurrence of spontaneous labor in primiparous women in physiological pregnancy. Moreover, it was assumed that the technique of traction on the cervical intervertebral spaces between the base of the occipital bone (C0) and the first cervical vertebra (C1) will release and optimize the functioning of the vagus nerve, and consequently accelerate perinatal maturation of the cervix, thus favorably preinducing the delivery. Method: In the research work, the comparative studies were the operational basis, and they were also cross-sectional studies, which consisted of observation. An objective tool - the Bishop scale - was used in the examination of the perinatal cervix maturity. 70 women with physiological pregnancy, 39 + 0 Hbd were qualified for the analysis. Results: The comparative analysis of the subjects showed a statistically significant differentiation in the evaluation of the cervical maturity in favor of GE women, which additionally gave birth closer to the date. Similarly, in the area of opening parameters, shortening of the cervix and the position of the leading point, women performed better on the background of the GK. Conclusion: In comparative studies, it was revealed that traction of the vagus nerve accelerates perinatal maturity of the cervix and spontaneous systolic function occurred closer to the planned date of delivery. The traction of the vagus nerve has a significant impact on the parameter of shortening, opening and lowering of the point of the leading cervix in assessing its perinatal maturity.